The temperature-dependent expression of type II secretion system controls extracellular product secretion and virulence in mesophilic Aeromonas salmonida SRW-OG1 - Yi, Xin; Chen, Yunong; Cai, Hongyan; Wang, Jiajia; Zhang, Youyu; Zhu, ZhiQin; Lin, Mao; Qin, Yingxue; Jiang, XingLong; Xu, Xiaojin (Frontiers in Cellular and Infection Microbiology, 2022)
Aeromonas salmonicida is a typical cold water bacterial pathogen that causes furunculosis in many freshwater and marine fish species worldwide. In our previous study, the pathogenic A. salmonicida (SRW-OG1) was isolated from a warm water fish, Epinephelus coioides was genomics and transcriptomics analyzed. Type II secretion system was found in the genome of A. salmonicida SRW-OG1, while the expressions of tatA, tatB, and tatC were significantly affected by temperature stress. Also, sequence alignment analysis, homology analysis and protein secondary structure function analysis showed that tatA, tatB, and tatC were highly conservative, indicating their biological significance. In this study, by constructing the mutants of tatA, tatB, and tatC, we investigated the mechanisms underlying temperature-dependent virulence regulation in mesophilic A. salmonida SRW-OG1. According to our results, tatA, tatB, and tatC mutants presented a distinct reduction in adhesion, hemolysis, biofilm formation and motility. Compared to wild-type strain, inhibition of the expression of tatA, tatB, and tatC resulted in a decrease in biofilm formation by about 23.66%, 19.63% and 40.13%, and a decrease in adhesion ability by approximately 77.69%, 80.41% and 62.14% compared with that of the wild-type strain. Furthermore, tatA, tatB, and tatC mutants also showed evidently reduced extracellular enzymatic activities, including amylase, protease, lipase, hemolysis and lecithinase. The genes affecting amylase, protease, lipase, hemolysis, and lecithinase of A. salmonicida SRW-OG1 were identified as cyoE, ahhh1, lipA, lipB, pulA, HED66_RS01350, HED66_RS19960, aspA, fabD, and gpsA, which were notably affected by temperature stress and mutant of tatA, tatB, and tatC. All above, tatA, tatB and tatC regulate the virulence of A. salmonicida SRW-OG1 by affecting biofilm formation, adhesion, and enzymatic activity of extracellular products, and are simultaneously engaged in temperature-dependent pathogenicity.